2021
DOI: 10.1371/journal.pone.0243788
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1 is a prerequisite for the development of cardiac hypertrophy and left ventricular dysfunction in mice upon transverse aortic constriction

Abstract: The CX3CL1/CX3CR1 axis mediates recruitment and extravasation of CX3CR1-expressing subsets of leukocytes and plays a pivotal role in the inflammation-driven pathology of cardiovascular disease. The cardiac immune response differs depending on the underlying causes. This suggests that for the development of successful immunomodulatory therapy in heart failure due to chronic pressure overload induced left ventricular (LV) hypertrophy, the underlying immune patterns must be examined. Here, the authors demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
5
17
0
Order By: Relevance
“…Bromodeoxyuridine (BrdU) FACS analysis showed that the proliferation of cardiac resident macrophages peaked at 3 days after TAC injury, whereas the proliferation of total macrophages peaked at 7 days after TAC surgery (Figure 1B, bottom panel) (Liao et al, 2018). In blood, both Ly6C high and Ly6C low monocytes peaked at 7 days after TAC surgery and then went back to the baseline in 3 to 4 weeks (Figure 1C, upper and bottom panels) (Weisheit et al, 2014(Weisheit et al, , 2021Patel et al, 2017). Yet, limited information is available from many other innate immune cells regarding their cardiac infiltration.…”
Section: Innate Immune Cellsmentioning
confidence: 92%
See 4 more Smart Citations
“…Bromodeoxyuridine (BrdU) FACS analysis showed that the proliferation of cardiac resident macrophages peaked at 3 days after TAC injury, whereas the proliferation of total macrophages peaked at 7 days after TAC surgery (Figure 1B, bottom panel) (Liao et al, 2018). In blood, both Ly6C high and Ly6C low monocytes peaked at 7 days after TAC surgery and then went back to the baseline in 3 to 4 weeks (Figure 1C, upper and bottom panels) (Weisheit et al, 2014(Weisheit et al, , 2021Patel et al, 2017). Yet, limited information is available from many other innate immune cells regarding their cardiac infiltration.…”
Section: Innate Immune Cellsmentioning
confidence: 92%
“…A series of studies illustrated that SAC surgery in rats induced myocardium macrophage infiltration and fibroblast activation at the early phase of hypertrophy (Kuwahara et al, 2003(Kuwahara et al, , 2004. TAC-induced cardiac hypertrophy exhibited expansion of circulating Ly6C high and Ly6C low monocytes and pro-inflammatory CD206 − cardiac macrophages at 1 week after surgery, prior to significant cardiac hypertrophy and dysfunction (Weisheit et al, 2014(Weisheit et al, , 2021Nemska et al, 2016;Patel et al, 2017Patel et al, , 2018Liao et al, 2018; Figure 1B). Recent studies showed that peripheral monocytes from hypertension patients with or without LV hypertrophy also underwent phenotypic alterations.…”
Section: Monocyte and Macrophage Functions In Pressure Overload-induced Cardiac Hypertrophy And Fibrosismentioning
confidence: 92%
See 3 more Smart Citations